web analytics

Ex 3.3, 6 - Prove that cos (pi/4 - x) cos (pi/4 - y) - Chapter 3 - (x + y) formula

  1. Chapter 3 Class 11 Trigonometric Functions
  2. Serial order wise
Ask Download

Transcript

Ex 3.3, 6 Prove that: cos (π/4−𝑥) cos (π/4−𝑦) – sin (π/4−𝑥) sin (π/4−𝑦) = sin⁡(𝑥 + 𝑦) Taking L.H.S We know that cos (A + B) = cos A cos B – sin A sin B The equation given in Question is of this form Hence A = ( 𝜋/4 −𝑥) B = ( 𝜋/4 −𝑦) Hence cos (π/4−𝑥) cos (π/4−𝑦) – sin (π/4−𝑥) sin (π/4−𝑦) = cos [(π/4−𝑥)" " +(π/4 −𝑦)] = cos [π/4−𝑥+π/4 −𝑦] = cos [π/4+π/4−𝑥−𝑦] = cos [π/2 −(𝑥+𝑦) ] Putting π = 180° = cos [(180°)/2 −(𝑥+𝑦) ] = cos [90° −(𝑥+𝑦) ] = sin (𝑥+𝑦) = R.H.S Hence proved

About the Author

CA Maninder Singh's photo - Expert in Practical Accounts, Taxation and Efiling
CA Maninder Singh
CA Maninder Singh is a Chartered Accountant for the past 8 years. He provides courses for Practical Accounts, Taxation and Efiling at teachoo.com .
Jail